Morphology of Peripheral Vitreoretinal Interface Abnormalities Imaged with Spectral Domain Optical Coherence Tomography - Rachel L. Chu; Nicole A. Pannullo; Christopher R. Adam; Mohammad R. Rafieetary; Eric J. Sigler (Journal of Ophthalmology)
The objective of this study is to describe the clinical utility and morphologic characteristics of peripheral vitreoretinal interface abnormalities with spectral domain optical coherence tomography (SD-OCT). A prospective imaging analysis of 43 patients with peripheral vitreoretinal interface abnormalities seen on binocular indirect examination with scleral indentation was done. SD-OCT was evaluated for image quality and structural findings. Laser retinopexy was performed to surround all retinal breaks containing a full-thickness component via SD-OCT. Acceptable image quality for inclusion was obtained in 39/43 (91%) patients. Mean age was 41 ± 22 years, and mean follow-up was 14 ± 1.6 months. Decision to treat was altered following SD-OCT in 5% of the patients. Two cases of previously diagnosed operculated holes were found on SD-OCT to be partial-thickness operculated breaks or focal operculated schisis. Peripheral SD-OCT is a reliable and useful technique to examine the structural features of vitreoretinal interface abnormalities in vivo. This imaging modality is useful in the clinical management of suspected retinal breaks identified with indirect ophthalmoscopy.